Effects of Tree Trunk, Branch and Leaf Traits On Morphological Diversity of Litchi Chinensis Sonn. - Abhay Kumar , Narayan Lal; Pandey , SD (Bangladesh Journal of Botany, 2023)
Twenty five morphological traits of tree trunk, branch and leaf were employed to discriminate 30 Indian Litchi (Litchi chinensis Sonn.) genotypes as well as to assess their morphological diversity at ICAR-NRC on Litchi, Muzaffarpur, India. Litchi genotypes were highly diversified. Twelve qualitative and 13 quantitative traits exhibited high degrees of variability. High phenotypic and genotypic coefficients of variation were recorded for tree volume (31.26 and 31.15%), leaf area (22.27 and 21.87%) and thickness of leaf (21.56 and 20.89%). High heritability coupled with high genetic advances was recorded for plant height (97.92%), crown diameter (99.40%), tree volume (99.34%), leaflet number (93.28%), rachis length (91.45%), petiole length (96.45%), petiolule length (95.91%), leaf length (93.07%), leaf area (96.39%) and leaf thickness (93.89%), indicating ample scope of improvement for these traits through selection. Bangladesh J. Bot. 52(1): 197-202, 2023 (March)